Utilizing Google Sites as a Physics Learning Platform for Solar System Topics - Susanti; Lutfi, Zulfa Amelia; Listiyani, Laily Rochmawati; Ernawati, Tias (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This research aims to develop learning media based on the Google site on the solar system. This type of research is development research using a 4-D model which consists of four stages, namely definition, design, development and dissemination. The data collection instruments in this research were validation sheets and student response questionnaires. The data analysis technique in this research uses data analysis from the validation of learning media and analysis of the practicality of learning media. The results of the research show that the Google Site web-based learning media on solar system material is suitable for use in learning with the ideal percentage of the product as follows: 1) The ideal percentage of the Google Site web-based learning media product on Solar System material in terms of the material aspect is 81.20% with the valid category ; 2) the ideal percentage of web-based learning media products on the Google site solar system material in terms of the media aspect is 83% with the valid category; and 3) the percentage of practicality of Google site web-based learning media products regarding the solar system is 88.40% in the practical category.